Long Chain Polyunsaturated Fatty Acids Docosahexaenoic Acid and Arachidonic Acid Supplementation in the Suckling and the Post-weaning Diet Influences the Immune System Development of T Helper Type-2 Bias Brown Norway Rat Offspring - Patel, Dhruvesh; Newell, Marnie; Goruk, Susan; Richard, Caroline; Field, Catherine J. (Frontiers in Nutrition, 2021)
Background: Dietary long chain polyunsaturated fatty acids (LCPUFA) such as arachidonic acid (ARA) and docosahexaenoic acid (DHA) play an important role in the development of the infant immune system. The role of LCPUFA in T helper type 2 (Th2) biased immune system is unknown. We aimed to understand the effect of feeding LCPUFA during suckling and post-weaning on immune system development in Th2 bias Brown Norway rat offspring. Methods: Brown Norway dams were randomly assigned to nutritionally adequate maternal diet throughout the suckling period (0-3 weeks): control diet (0% ARA, 0% DHA; n=8) or ARA+DHA (0.45% ARA, 0.8% DHA; n=10). At 3 weeks, offspring from each maternal diet groups were randomized to either a control (0% ARA, 0% DHA; n=19) or ARA+DHA post-weaning (0.5% ARA, 0.5% DHA; n=18) diets. At 8 weeks, offspring were killed, and tissues collected for analyzing immune cell function and fatty acid composition analyses. Results: ARA+DHA maternal diet resulted in higher (P < 0.05) DHA composition in breast milk (4x) without changing ARA levels. This resulted in more mature adaptive immune cells in spleen ([T regulatory (Treg) cells and B cells]), mesenteric lymph nodes (MLN, lower CD45RA+) and Peyer’s patches (PP; higher IgG+, B cells), in the ARA+DHA group offspring at 8 weeks. ARA+DHA post-weaning diet (3-8 weeks) resulted in 2x higher DHA in splenocyte phospholipids compared to control. This also resulted in higher Th1 cytokines, approximately 50% higher TNFαTNF-α and IFN, by PMAi stimulated splenocytes ex-vivo, with no differences in Th2 cytokines (IL-4, IL-13 and IL-10) compared to controls. Conclusion: Feeding dams a diet higher in DHA during suckling period resulted in adaptive immune cell maturation in offspring at 8 weeks. Providing ARA and DHA during the post-weaning period in a Th2 biased Brown Norway offspring model may supports Th1 biased immune response development, which could be associated with lower risk of developing atopic diseases.